2017
DOI: 10.1016/j.celrep.2017.05.081
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-Linked Phosphorylation of the FANCI S/TQ Cluster Contributes to Activation of the Fanconi Anemia I/D2 Complex

Abstract: SUMMARY Repair of interstrand crosslinks by the Fanconi anemia (FA) pathway requires both the monoubiquitination and de-ubiquitination of the FANCI/FANCD2 (FANCI/D2) complex. In the standing model, the phosphorylation of six sites in the FANCI S/TQ cluster domain occurs upstream of, and promotes, FANCI/D2 monoubiquitination. We generated phospho-specific antibodies against three different S/TQ cluster sites (Serines 556, 559, and 565) on human FANCI and found that, in contrast to the standing model, distinct F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 22 publications
(44 reference statements)
3
58
1
Order By: Relevance
“…This raised questions regarding the accessibility of ubiquitin and E3 enzyme into the dimer during the conjugation reaction. In contrast, several validated ATR kinase sites of FANCI (S556, 559, and 565) within an ST/Q cluster (Chen et al, 2015;Cheung et al, 2017) were found to be exposed on the FANCI surface adjacent to the heterodimer interface (Joo et al, 2011). As ATR kinase activity is required for optimal FANCD2 monoubiquitination (Shigechi et al, 2012), it was proposed that ATR phosphorylation of FANCI occurs prior to FANCI:FANCD2 ubiquitination to promote a partial opening of the FANCI:FANCD2 complex, and access to the ubiquitin ligase complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raised questions regarding the accessibility of ubiquitin and E3 enzyme into the dimer during the conjugation reaction. In contrast, several validated ATR kinase sites of FANCI (S556, 559, and 565) within an ST/Q cluster (Chen et al, 2015;Cheung et al, 2017) were found to be exposed on the FANCI surface adjacent to the heterodimer interface (Joo et al, 2011). As ATR kinase activity is required for optimal FANCD2 monoubiquitination (Shigechi et al, 2012), it was proposed that ATR phosphorylation of FANCI occurs prior to FANCI:FANCD2 ubiquitination to promote a partial opening of the FANCI:FANCD2 complex, and access to the ubiquitin ligase complex.…”
Section: Introductionmentioning
confidence: 99%
“…As ATR kinase activity is required for optimal FANCD2 monoubiquitination (Shigechi et al, 2012), it was proposed that ATR phosphorylation of FANCI occurs prior to FANCI:FANCD2 ubiquitination to promote a partial opening of the FANCI:FANCD2 complex, and access to the ubiquitin ligase complex. Support for this comes from the observation that FANCI phosphorylation at serine sites 559 and 565 occurs predominantly on the monoubiquitinated form (Cheung et al, 2017). The UAF1-binding SIM domain of FANCI is next to serines 559 and 565, so an alternative explanation is that ATR acts on these sites post-monoubiquitination, to prevent USP1:UAF1 binding.…”
Section: Introductionmentioning
confidence: 99%
“…ATR-mediated FancI phosphorylation at Serine 556 (called ubiquitination-independent phosphorylation) occurs predominantly upstream of, and promotes, the monoubiquitination of FancD2/FancI (7, 62). On the other hand, FancI Serine 565 phosphorylation (called ubiquitination-linked phosphorylation) occurs downstream of Ub-FancD2/I and inhibits FancD2 de-ubiquitination (7). Augmented ATR activity in E6 expressing cells resulted in increased phosphorylation of FancI at both sites S556 and S565.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was prepared for mass-spec as previously described (Rajan et al, 2017). Immunoprecipitates were electrophoresed approximately one to two centimeters into a SDS-PAGE gel, and the stained gel band was cut out and proteolytically 20 digested with trypsin as described (Cheung et al, 2017). Desalted peptides were subjected to LC-MS/MS with an OrbiTrap Elite mass spectrometer, and collected data were analyzed by Proteome Discoverer v2.2.…”
Section: Immunoprecipitation and Mass Spectrometrymentioning
confidence: 99%